2020
DOI: 10.3390/rel11030128
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Bibliotherapy in Revealing and Addressing the Spiritual Needs of Cancer Patients

Abstract: Assessing and addressing spiritual needs is a key factor in the quality of life and overall wellbeing of cancer patients. However, the evolution and diversification of assessment tools has not automatically been followed by their successful implementation; thus, addressing unmet needs continues to be a concern. In this paper, we examine the place of bibliotherapy (also called reading therapy or poetry therapy) as a group intervention in the oncological setting in revealing spiritual needs. We show that it repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This study found that more than half of respondents engage in interventions that include various aspects of spirituality beyond religiosity. However, the intervention "reading books and other publications to patients" is only undertaken by a small percentage of participants (just over 10%), despite research demonstrating its benefits to patient well-being [32][33][34]. A systematic literature review demonstrates how nurses highlight shortcomings in their initial nursing education, expressing a need for additional training, comprehension, and professional support to recognise and deliver spiritual care effectively [35].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that more than half of respondents engage in interventions that include various aspects of spirituality beyond religiosity. However, the intervention "reading books and other publications to patients" is only undertaken by a small percentage of participants (just over 10%), despite research demonstrating its benefits to patient well-being [32][33][34]. A systematic literature review demonstrates how nurses highlight shortcomings in their initial nursing education, expressing a need for additional training, comprehension, and professional support to recognise and deliver spiritual care effectively [35].…”
Section: Discussionmentioning
confidence: 99%
“…Stories could affect human emotions, and books can be a model for selfdevelopment because they affect emotions [34]. Bibliotherapy can also be a medium for individuals to find their spiritual needs [21].…”
Section: Encouragement Of Resilience To the Covid-19 Pandemic In Preg...mentioning
confidence: 99%
“…A similar study used qur'anic therapy to increase religious coping of hemodialysis patients [15] Since 2002 and improve the mental health and well-being of psychology of lesbian prisoners [16], [17]. Interventions using bibliotherapy through guided reading with therapeutic results in mind become evidence that bibliotherapy can be used to enhance therapy [18], promote good mental and emotional health [19], reduce anxiety and sadness [20], can help identify spiritual needs [21], create a new frame of perception of the situation at hand through fiction and non-fiction reading, thereby encouraging new meanings of life [22].…”
Section: Introductionmentioning
confidence: 99%
“…Bibliotherapy is an intervention that "uses literary texts and guided group discussion to promote selfunderstanding, cognitive, emotional, behavioral, and spiritual change in patients" [9]. It is built on self-help books and applies either cognitive or behavioral therapy, with a special focus on the unconscious, emotional, and spiritual aspects of human beings [10].For over a century, bibliotherapy has been widely applied in various therapies among various populations with various conditions to support healing and well-being [11].…”
Section: Introductionmentioning
confidence: 99%